Remarks from World Bank Group President David Malpass at the G20 Leaders Summit - Malpass, David (World Bank, Washington, DC, 2019)
These remarks were delivered by David Malpass, President of the World Bank Group, at the G20 Leaders Summit held in Osaka, Japan. He spoke about how giving women better access to economic opportunities is critical to eliminate differences in living standards between men and women. He highlighted We-Fi which is so important and how the Bank was proud to celebrate its two-year anniversary in Osaka. He spoke about the developing countries and the Bank's role in actively identifying changes in the private sector environment that will attract investment and enable higher living standards and better lives. He explained the Bank's work in fragile states, such as the Sahel and the Horn of Africa, to help countries build stronger foundations so that young people are more able to stay rather than seeking to immigrate. He discussed reducing inequality and realizing inclusive and sustainable growth around the world, and how addressing these requires jobs, education, healthcare, attention to the environment, and robust commerce and trade among neighbors and nations. He concluded by saying that the Bank would continue to work with all the nations on these challenges.